Exploring mental health experience in individuals living with temporomandibular disorders - Wafaa Safour; Richard Hovey (The Beryl Institute, 2021)
Despite the evidence supporting deteriorating mental health because of temporomandibular disorders (TMDs) conditions, there is limited evidence of TMD patients' experience regarding how their mental health is affected by the disorders. As a sequence of these conditions, TMD patients suffer from physical and mental complications, not to mention the loss of food enjoyment. In this study, we aim to explore TMD patients' lived experiences who had changed their dietary habits concerning their mental health. Six participants were interviewed to answer open-ended questions during semi-structured interviews regarding their mental health experiences with TMD-related food routine changes. These interviews were held face-to-face with the participants and were recorded and transcribed. Interpretive phenomenology was used to organize and analyze the narrative data collected. We identified three themes amongst participants who have concerns about their mental health that included (i) depraving of favored food, (ii) rethinking in all aspects of their life, and (iii) fear of future. For each of these themes, the participants' mental health was affected by TMD's pain due to diet changes, consequently, lifestyle, daily activities, and hopefulness for a cure. The participants' mental health was mostly unaddressed by their healthcare providers. Our findings highlight the need for healthcare providers to establish nutritional guidelines for TMD individuals at risk of psychological and physiological comorbidities. Also, the need for healthcare for intervention programs to treat people living with chronic TMD pain. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.